SONIA GUIMARÃES - ENGLISH VERSION - Rosa, Katemari Diogo da (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Sonia Guimarães, born in São Paulo in 1956, daughter of a upholsterer and a housewife, was always the second in the class in all subjects and was passionate about teachers of Mathematics, Physics and Chemistry. In 1974, she finished high school and then entered the São Paulo High School of Arts and Crafts, where she took the technical course in buildings. She enters the Bachelor of Science course at the Federal University of São Carlos (UFSCar) and concludes it in 1979. Then, in 1983, she completed her master's degree in Applied Physics at the São Carlos Institute of Physics and Chemistry, University of São Paulo (USP). In 1989, Sonia obtained a Ph.D. in electronic materials from the University of Manchester Institute of Science and Technology. In 1993, Sonia became a professor of physics at the Technological Institute of Aeronautics (ITA). (ITA). She is currently an employee of the Ministry of Defense of Brazil, in the Department of Aerospace Science and Technology (DCTA), as an adjunct professor at ITA.